Pengaruh Opini Audit Tahun Sebelumnya dan Kondisi Keuangan terhadap Opini Audit Going Concern - Iin Rosini (Pusat P2M Politeknik Negeri Batam, 2017)
This study examines whether the variable prior year's audit opinion and the financial condition of the going concern audit opinion on manufacturing companies. The study sample was sub sectors of food and beverages that are listed in the Indonesia Stock Exchange. Total 12 companies in 2010-2014. The sampling method used in this research is purposive sampling, the data processing methods and processing logistic regression analysis with SPSS version 22. The results of this study show that the previous year's audit opinion positive significant effect on the provision of going concern audit opinion and does not affect the company's financial condition significant at manufacturing companies.